Exploring links between oral health and infective endocarditis - Joseph Luke Falconer; Joseph Luke Falconer; Ronak Rajani; Vitaliy Androshchuk; Amieth Yogarajah; Rebecca A. Greenbury; Ayden Ismail; Natasha Oh; Luigi Nibali; Luigi Nibali; Eleanor M. D'Agostino; Vanessa Sousa; et al. (Frontiers Media S.A., 2024)
Infective endocarditis (IE) is a bacterial infection of the heart's inner lining. A low incidence rate combined with a high mortality rate mean that IE can be difficult to treat effectively. There is currently substantial evidence supporting a link between oral health and IE with the oral microbiome impacting various aspects of IE, including pathogenesis, diagnosis, treatment, and mortality rates. The oral microbiome is highly diverse and plays a crucial role in maintaining oral health by providing protective functions. However, when dysbiosis occurs, conditions such as periodontal or peri-implant disease can arise, offering a pathway for bacteraemia to develop. The role of the oral microbiome as a coloniser, facilitator and driver of IE remains to be uncovered by next-generation sequencing techniques. Understanding the dysbiosis and ecology of the oral microbiome of IE patients will allow improvements into the diagnosis, treatment, and prognosis of the disease. Furthermore, an increased awareness amongst those at high-risk of developing IE may encourage improved oral hygiene methods and lower incidence rates. This narrative review examines current findings on the relationship between oral health and IE. It draws from key studies on both topics, with manuscripts selected for their pertinence to the subject. It highlights the link between the oral microbiome and IE by exploring diagnostic techniques and treatments for IE caused by oral commensals.